Historians at the Frankfurt Auschwitz Trial Their Role As Expert Witnesses - Turner, Mathew 1980- (I. B. Tauris & Company, Limited, 2018)
Cover -- Author Biography -- Title page -- Copyright -- Dedication -- Contents -- List of Plates -- Acknowledgements -- Introduction -- The Expert Witness Historian -- Plausible versus Probable: History and Law -- Locating the Paradox: Historical Knowledge as Legal Evidence -- The Frankfurt Auschwitz Trial Experts: Existing Literature -- Praising Anatomy -- Book Structure and Chapter Synopsis -- 1. Background to Frankfurt: The IfZ, Gutachten and the Ulm Trial -- Gutachten and the Institut fu¨r Zeitgeschichte -- The Ulm Einsatzkommando Trial -- 2. The Law Courts History: Pre-Trial Preparations -- A Perfect Sturm: Bauer and the IfZ, 1959-1962 -- A Perfect Sturm: Bauer and the IfZ, 1959-1962 -- Drafting the Gutachten -- 'Gutachten are worthless here': A Judge's Pre-Trial Verdict -- 3. Giving Evidence: The Historians' Court? Or, Historians Caught? -- 'An Historical Seminar': Buchheim, 7 February 1964 -- The Director's Drama: Krausnick, 17 February 1964 -- 'Compassion has no place': Broszat, 21 and 28 February 1964 -- Buchheim Returns, 3 July 1964 -- The Last Chapter: Jacobsen, 14 August 1964 -- 4. Judgement Day: Hofmeyer Reaches a Verdict -- Parting Shots: Kaul and Laternser -- Hofmeyer's Final Judgement -- Judging History, Making Law: How the Historians Fared -- 5. Publishing Anatomy: Gutachten to Chapters -- The Paperback Gutachten -- 'A Guide to Barbarism' -- 6. Responding to Anatomy: Scholars React -- Reviewing Anatomy: English Take the Lead -- Dissecting Anatomy: The Future of the Past -- The 'Burning Questions': Herzfeld and Ainsztein -- 7. Receiving Anatomy: How the Book Made History -- Laternser's Lies -- The Road to Auschwitz -- The Debate Begins: Krausnick versus Broszat -- Creating History, Informing Research -- Conclusion -- Notes -- Bibliography -- Index.